Scleral Buckling for Retinopathy of Prematurity: A Case Report: Presentation - Case Report - Resident - Permanik, Gustiandari Fidhya; Barliana, Julie Dewi; Yudantha, Anggun Rama (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinopathy of prematurity (ROP) is a vasoproliferative retinal disease that affects premature infants. Patients with advanced ROP require surgery to minimize retinal distortion and prevent total retinal detachment. This case reports the efficacy of scleral buckling (SB) in a patient with stage 4B ROP in both eyes within 3 months. Case Illustration : A 4-month-old female baby presented to the Pediatric Ophthalmology Division in Cipto Mangunkusumo Hospital with the chief complaint of no eye contact in both eyes. Her eyes moved by themselves since the age of 3.5 months and sometimes looked crossed. The patient presented to the pediatrician and was referred to the pediatric ophthalmology division for further management. There was a history of premature delivery at 30 weeks with oxygen therapy for 3 weeks. Pediatric Ophthalmology Division performed ultrasonography and Retcam and diagnosed ROP stage 4B in both eyes. Scleral buckling was performed by vitreoretinal division in the right and left eyes at 49 and 52 weeks postmenstrual age, respectively. Discussion : Vitrectomy and scleral buckling are the surgical options in advanced ROP. Vitrectomy is ideally performed in stage 4A without macular involvement. We considered performing SB because vitrectomy seems to be ineffective in this patient and the patient is more prone to intraocular complications. Conclusion : Scleral buckling is effective in preventing further progression of retinal detachment, reducing vitreoretinal traction and preventing ischemia in the retinal detachment. In short-term follow-up, we found no worsening of progression. However, further follow-up is needed to demonstrate the long- term efficacy of SB in advanced ROP.